Pilot scale oxidative fast pyrolysis of sawdust in a fluidized bed reactor: A biorefinery approach. (December 2020) - Karmee, Sanjib Kumar; Kumari, Geeta; Soni, Bhavin
Highlights: A fast pyrolysis system (3 kg/h capacity) was designed and developed at SPRERI. Oxidative fast pyrolysis was performed at 0.20 equivalence ratio and 550 °C. Bio-oil was characterized using GC–MS, NMR ( 1 H and 13 C), CHNSO and FTIR. Ea of sawdust and char were found to be 113 kJ/mol and 46.92 kJ/mol respectively. Pyro-gas is composed of N2, CO, CO2, H2, O2, and CH4 . Abstract: Oxidative fast pyrolysis of sawdust was performed in a pilot scale fluidized bed system (3 kg/h) under stabilized experimental conditions (0.20 equivalence ratio and 550 °C). Experiments were performed in non-catalytic and catalytic (ZSM-5) mode. During non-catalytic fast pyrolysis, bio-oil (∼38 wt%), bio-char (∼12 wt%) and pyro-gas (∼50 wt%) were obtained; in contrast, for catalytic fast pyrolysis bio-oil, bio-char and pyro-gas yields were ∼44 wt%, ∼4 wt% and ∼52 wt% respectively. The obtained bio-oil was characterized through CHNSO, NMR ( 1 H and 13 C NMR), FT-IR and GC–MS techniques. GC–MS analysis of the bio-oil shows it is a mixture of ∼21 chemical compounds. Furthermore, NMR ( 1 H and 13 C NMR) and FT-IR results indicates presence of hydrocarbon, alcohol, phenol and aldehyde in the bio-oil. The TGA of bio-char shows that it is stable up to 950 °C. The activation energies (Ea ) of sawdust and bio-char are found to be 112.3 kJ/mol and 46.92 kJ/mol respectively. FT-IR analysis of bio-char clearly revealed removal of functionalized organic compounds during devolatilization of sawdust. In addition, GC analysis of pyro-gas suggests that it is a mixture of N2 (35.55 vol%), CO (34.49 vol%), CO2 (16.80 vol%), H2 (4.54 vol%), O2 (4.25 vol%), and CH4 (4.41 vol%).